2014
DOI: 10.1002/ajim.22297
|View full text |Cite
|
Sign up to set email alerts
|

Examining occupational health and safety disparities using national data: A cause for continuing concern

Abstract: Background Occupational status, a core component of socioeconomic status, plays a critical role in the well-being of U.S. workers. Identifying work-related disparities can help target prevention efforts. Methods Bureau of Labor Statistics workplace data were used to characterize high-risk occupations and examine relationships between demographic and work-related variables and fatality. Results Employment in high-injury/illness occupations was independently associated with being male, Black, ≤high school de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
63
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 20 publications
5
63
2
2
Order By: Relevance
“…Another significant finding from this study relates to Hispanic youth ages 15-17 who had higher fatality rates than their white counterparts. While this is consistent with past studies [Estes et al, 2010;Steege et al, 2014], our findings also revealed foreign-born youth, the majority of whom come from Mexico and Central America, were at the greatest risk of suffering an occupational fatality when compared to those born in the US. Consistent with prior studies, our results showed transportation incidents and vehicles are the number one event/exposure and source, respectively, of fatal injury to teens [Dunn and Runyan, 1993;Estes et al, 2010;Rauscher et al, 2011;Steege et al, 2014].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Another significant finding from this study relates to Hispanic youth ages 15-17 who had higher fatality rates than their white counterparts. While this is consistent with past studies [Estes et al, 2010;Steege et al, 2014], our findings also revealed foreign-born youth, the majority of whom come from Mexico and Central America, were at the greatest risk of suffering an occupational fatality when compared to those born in the US. Consistent with prior studies, our results showed transportation incidents and vehicles are the number one event/exposure and source, respectively, of fatal injury to teens [Dunn and Runyan, 1993;Estes et al, 2010;Rauscher et al, 2011;Steege et al, 2014].…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with prior studies [Estes et al, 2010], we found the rate of occupational fatalities among 15-to 17-year-olds has dropped since 2001. Our findings also suggest the gender differences seen in past studies of teen occupational fatalities [Dunn and Runyan, 1993;Higgins et al, 2002;Estes et al, 2010;Rauscher et al, 2011;Steege et al, 2014] continue to persist, with 15-to 17-year old males experiencing a significantly higher fatality rate compared to females. Another significant finding from this study relates to Hispanic youth ages 15-17 who had higher fatality rates than their white counterparts.…”
Section: Discussionsupporting
confidence: 77%
“…Analyses combining all study variables indicated injury rates were highest among workers aged over 30 from the new European Union nations and ‘other’ countries, and employed in sectors categorised as low risk by the authors. Thus, in agreement with other researchers, the authors confirm that variables relevant to the study of occupational injury in foreign-born workers include age, industry,2 length of time of residence,3 and region4 or country of origin 3…”
supporting
confidence: 91%
“…The increased risk of mortality in food production has also been established by other researchers. 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Use that differs within an industry may be associated with occupational health disparities. 37 For example, though tractor roll-over fatalities are a well-documented hazard for agricultural workers, only an estimated 59% of tractors in operation are equipped with roll-over protection, 38 and the prevalence of such protection is lower among lower income farmers. 36,39 .…”
Section: Discussionmentioning
confidence: 99%